A Field Study of New Employee Training Programs: Industry Practices and Strategic Insights. (November 2015) - Tracey, J. Bruce; Hinkin, Timothy R.; Tran, Thao Li Bui; Emigh, Teresa; Kingra, Michael; Taylor, Jonathan; Thorek, David
Given the importance of well-designed and well-executed training programs, it is important to learn more about the content and design of effective training programs for new employees, particularly those that have been implemented in the hospitality industry. Through a field study assessment of pre-opening training programs that have been implemented by fifteen hotel firms and sixteen restaurant companies, we found that hotels and restaurants spend approximately the same time on pre-opening training for new staff, with the exception of restaurant managers, who receive significantly more days of training than do their hotel counterparts. In addition, there were substantive differences in the amount of pre-opening training based on firm size and whether the company was publicly traded or privately held. We also found that the majority of pre-opening training is designed and delivered by corporate staff, and a balance of active and passive training methods are used for facilitation. Finally, although our survey methodology did not allow us to determine the costs associated with pre-opening training (and therefore the return on these efforts), we noted that the firms used guest satisfaction measures and measured the employees' content mastery, among other metrics.